2006
DOI: 10.1143/jjap.45.l659
|View full text |Cite
|
Sign up to set email alerts
|

Blue, Green, and Amber InGaN/GaN Light-Emitting Diodes on Semipolar {11-22} GaN Bulk Substrates

Abstract: We demonstrate the fabrication of blue, green, and amber InGaN/GaN light-emitting diodes (LEDs) on semipolar {11-22} bulk GaN substrates. The {11-22}GaN substrates used in this study are produced by cutting out from a c-oriented GaN bulk crystal grown by hydride vapor epitaxy. The LEDs have a dimension of 320 ×320 µm2 and are packed in an epoxide resin. The output power and external quantum efficiency (EQE) at a driving current of 20 mA are 1.76 mW and 3.0%, respectively, for the blue LED, 1.91 mW and 4.1% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
296
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(305 citation statements)
references
References 17 publications
(20 reference statements)
7
296
1
1
Order By: Relevance
“…However, taking into account aggregate results of the above analysis, we have decided to choose the (1122) InGaN/GaN LEDs. Efficient long-wavelength emission of these devices has been also reported many times (see, e.g., [23][24][25][26][27]) and their structures seem to have currently more perspective advantages as green emitters [28] among reported orientations to date. In particular, expected highpower green (516 nm) emission has been reported by Sato et al [29] from the InGaN/GaN multi-quantum-well LED manufactured on the (1122) GaN substrate.…”
Section: Designing Of Nitride Leds With Reduced Polarization Effectsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, taking into account aggregate results of the above analysis, we have decided to choose the (1122) InGaN/GaN LEDs. Efficient long-wavelength emission of these devices has been also reported many times (see, e.g., [23][24][25][26][27]) and their structures seem to have currently more perspective advantages as green emitters [28] among reported orientations to date. In particular, expected highpower green (516 nm) emission has been reported by Sato et al [29] from the InGaN/GaN multi-quantum-well LED manufactured on the (1122) GaN substrate.…”
Section: Designing Of Nitride Leds With Reduced Polarization Effectsmentioning
confidence: 90%
“…For lower inclination angles ϑ , i.e. for semi-polar orientations, the overlapping depends on a distance of ϑ from its value (about 34 • ) corresponding to [20,21,23,26,27,29,31] the same polarizations in both the quantum well and the barrier (Fig. 6).…”
Section: Designing Of Nitride Leds With Reduced Polarization Effectsmentioning
confidence: 99%
“…The characteristic geometrical properties of the {100} surface are the surface terminated by a single atomic species 6,22 and two dangling bonds per atom on the surface. The same properties are indeed shared with 11 " 22 È É , but not any other wurtzite semipolar planes, as already seen in Fig.…”
Section: Surface Geometrymentioning
confidence: 99%
“…3-9 Especially, 11 " 22 À Á has attracted vast attention due to its strong ability to incorporate In, aiming for green-light emitters. 6,7 Ueda et al (the group led by Kawakami at Kyoto University) have been growing exclusively on the 11 " 22 À Á GaN substrates. 10 Stimulated emission in the green spectral region was recently achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, high efficiency green and yellow semipolar (11 22) InGaN LEDs grown on low threading dislocation density (TDD $ 5 Â 10 6 cm À2 ) high-cost (11 22) GaN bulk substrates have previously been demonstrated. 10,11 By means of time-resolved photoluminescence measurements (TR-PL), it has been experimentally reported that mplane InGaN 4 and (11 22) InGaN [12][13][14] QWs have shorter recombination lifetimes compared to polar QWs. However, it should be noted that those samples show recombination dynamics identical to those observed in polar QWs.…”
Section: Introductionmentioning
confidence: 99%